ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT PROFITABILITAS BANK KONVENSIONAL DI INDONESIA - , Johanes E.L. Makatita, Dr. Sumiyana, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research is to test how the influence of banks size (BS), non performing loan (NPL), operational cost (BOPO), capital adequacy ratio (CAR), loan to deposit ratio (LDR), and net interest margin (NIM) to profitability bank measured through return on assets (ROA), return on equity (ROE), and economic value added (EVA). The research methods using hypothesis testing with statistic tools of classic assumption, F- test, determination coefficient test, multiple regression test, and t-test. The sample of this research is a bank registered in IDX period 2012, and there are 31 banks. The results of this research showed that bankâs size (BS), non performing loan (NPL), operational cost (BOPO), and net interest margin (NIM) significant effect on the profitability (ROA, ROE) conventional banks in Indonesia period of 2012. Meanwhile, insignificant effect of capital adequacy ratio (CAR) and loan to deposit ratio (LDR) on profitability banks. While the independent variables (BS, NPL, BOPO, CAR, LDR, and NIM) were all insignificant effect on the level of bank profitability as measured by economic value added (EVA).